F67. NEUROCOGNITION IN 7-YEAR-OLD CHILDREN OF PARENTS WITH SCHIZOPHRENIA OR BIPOLAR DISORDER. (1st April 2018) - Hemager, Nicoline; Plessen, Kerstin; Thorup, Anne Amalie; Christiani, Camilla J; Ellersgaard, Ditte; Spang, Katrine Søborg; Burton, Birgitte Klee; Greve, Aja; Gantriis, Ditte L; Søndergaard, Anne; Gregersen, Maja; Mors, Ole; et al.
Abstract: Background: Children of parents with schizophrenia or bipolar disorder display neurocognitive deficits. However, studies of schizophrenia offspring and bipolar offspring at the same age are lacking. The objective was to compare neurocognitive abilities in 7-year-old children of parents with schizophrenia or bipolar disorder with neurocognitive abilities in children of parents without these disorders. Methods: In this nationwide cohort study we assessed 522 7-year-old children (schizophrenia offspring: N=202, bipolar offspring: N=120, and controls=200) with a detailed and well validated neurocognitive test battery. We compared the neurocognitive test scores of the three study groups. Results: Children of parents with schizophrenia showed neurocognitive deficits, whereas children of parents with bipolar disorder displayed neurocognitive abilities comparable to the control group. Discussion: Neurocognitive deficits are numerous in 7-year-old children of parents with schizophrenia, which supports the neurodevelopmental model of schizophrenia. Unimpaired neurocognitive abilities in children of parents with bipolar disorder indicate different neurodevelopmental manifestations in these high risk populations at this early age. Our results call for early identification of schizophrenia offspring with cognitive dysfunctions.